Curcumin activates Nrf2 through PKCδ-mediated p62 phosphorylation at Ser351 - Jee-Yun Park (Nature Portfolio, 2021)
Abstract Curcumin, a phytochemical extracted from Curcuma longa rhizomes, is known to be protective in neurons via activation of Nrf2, a master regulator of endogenous defense against oxidative stress in cells. However, the exact mechanism by which curcumin activates Nrf2 remains controversial. Here, we observed that curcumin induced the expression of genes downstream of Nrf2 such as HO-1, NQO1, and GST-mu1 in neuronal cells, and increased the level of Nrf2 protein. Notably, the level of p62 phosphorylation at S351 (S349 in human) was significantly increased in cells treated with curcumin. Additionally, curcumin-induced Nrf2 activation was abrogated in p62 knockout (−/−) MEFs, indicating that p62 phosphorylation at S351 played a crucial role in curcumin-induced Nrf2 activation. Among the kinases involved in p62 phosphorylation at S351, PKCδ was activated in curcumin-treated cells. The phosphorylation of p62 at S351 was enhanced by transfection of PKCδ expression plasmid; in contrast, it was inhibited in cells treated with PKCδ-specific siRNA. Together, these results suggest that PKCδ is mainly involved in curcumin-induced p62 phosphorylation and Nrf2 activation. Accordingly, we demonstrate for the first time that curcumin activates Nrf2 through PKCδ-mediated p62 phosphorylation at S351.